CREATION AND DESIGN OF TESTS BY ICT - Vdovychyn Т.В. (Journal of Information Technologies in Education (ITE), 2020)
The urgent task of teacher training in a certain profile is the formation of ICT competence for use in the learning process and future professional activities. The use of ICT will contribute to the formation of technological literacy, rational use of information resources, information culture of the future teacher. ICT skills will contribute to the positive development of the image of the modern teacher.The implementation of the acquired skills in the use of ICT in the practical activities of the future teacher allows first of all to present students with educational material. A quick and high-quality tool for future teachers is the use of electronic presentations, the possibilities of which are not limited to the presentation of educational information for students with animation effects. With the help of electronic presentations, you can organize the control of knowledge through questionnaires, testing or surveys of students.The article demonstrates the stages of designing tests with the help of electronic presentations, namely: creating a test with one or more correct answers, establishing correspondence between sets of questions and answers, determining the correct sequence of actions.This study focuses on the use of electronic presentations by students in the learning process not only to demonstrate educational material, but also the ability to organize knowledge control, which will contribute to the use of ICT for professional disciplines, teaching practice, individual tasks, writing term papers and qualifications.The use of electronic presentations by the teacher diversifies the learning process and helps to organize the student body. Possibilities of electronic presentations contribute to the formation of skills in the use of PCs in professional activities, as well as ICT competence and motivation of teachers of a certain profile.